Green Medicine: Exploring the Role of Herbal Treatments in Disease Therapy - Dean, Muhajirin (Manunggal Halim Jaya, 2024)
This study aims to investigate the perceptions, utilization, and integration of herbal treatments within contemporary healthcare systems. By adopting a qualitative research approach, this study primarily relies on an extensive literature review to gather and analyze data. The research seeks to provide a comprehensive understanding of how herbal medicine is perceived by patients and healthcare providers, how it is utilized across different cultural contexts, and the challenges associated with integrating herbal treatments into mainstream healthcare. The findings reveal that while herbal medicine is widely perceived as a natural and safer alternative to conventional pharmaceuticals, significant concerns remain regarding the standardization, quality control, and potential herb-drug interactions. The study also highlights the variability in the utilization of herbal treatments, with some regions relying heavily on traditional practices, while others use them as complementary therapies. The integration of herbal treatments into healthcare systems presents both opportunities and challenges, with a need for more robust clinical evidence and standardized protocols. The study concludes by emphasizing the importance of sustainable research that addresses these challenges and proposes future research directions, including community-based studies and the exploration of the environmental impact of herbal medicine. These findings contribute to the ongoing discourse on the role of herbal treatments in disease therapy and underscore the need for a multidisciplinary approach to advance the field.